Pengaruh Kebiasaan Menulis Menggunakan Kata Baku di Media Sosial Terhadap Keterampilan Menulis Mahasiswa di Perguruan Tinggi - Nanang Umam (Jurnal Bidang Pendidikan Dasar, 2022)
The purpose of this study in general is to determine the effect of the use of social media on students' writing skills. This study uses a qualitative and quantitative approach, a quasi-experimental type of research (quasi-experimental) with a non-equivalent control group design pattern. The data collection technique used in this research is a test with a test sheet instrument in written or essay form. The results showed that there was a significant difference between writing habits (using standard words) on social media and the writing skills of PGSD students at Muhammadiyah University of Gresik. This is because the degrees of freedom (df) are 25 with tcount > ttable, namely 5.251 > 2.342, so Ho is rejected and Ha is accepted.